Rhodamine-B Dyes Adsorption by Beads Alginate - Rahayu Rahayu; Adriani Bandjar; Ninditha Clourisa Amaris Susanto; Nguyen Thi Thanh Phuong; Febi Indah Fajarwati (Walisongo Journal of Chemistry, 2022)
Research has been carried out on the adsorption of rhodamine-b dye by alginate beads. The production of alginate granules was carried out at a concentration of 3.5% alginate powder. Identification of functional groups was carried out by FT-IR and water absorption test resulted in a maximum capacity of 96.24% at 90 minutes. Determination of adsorption capacity was carried out by UV-VIS spectrophotometer at a maximum contact time of 30 minutes and a maximum pH at pH 7, and resulted in adsorption maximum concentration at 30 ppm is 15.954 mg/L with adsorption capacity of 4.7862 mg/g